Assessment of Dental Caries among Internally Displaced Children in Baghdad - Alwaheb, Athraa M; Alhuwaizi, Akram F (Journal of Baghdad College of Dentistry, 2018)
Background: The internally displaced children are vulnerable groups have less access to dental services, worse oral health, and bear a disproportionate burden of oral diseases. Aim of the study: This study was conducted on group of internally displaced children living in Baghdad governorate camps to measure their dental caries prevalence and experience and find out the association between dental caries and the duration of displacement in camps.Subjects and methods: A sample of 1393 children were selected, 567 internally displaced children from camps in Baghdad governorate and 826 school children as control matching in age and gender. The age of children ranged from 5-12 years old. Oral examination was performed using WHO 2013 criteria, to measure dental caries using CPI probe. Results: There were a significant difference of dmfs and dmft between Internally displaced children and Schoolchildren. Caries free Internally displaced children were 39.2% and 30% among school children. There was no statistically significant correlation between camp duration and dental caries experience in deciduous teeth while a significant relation was found in permanent teeth. Conclusion: This study revealed an increase in dental caries experience with increase in duration of displacement. Hence this survey highlighted the need of internally displaced children to dental health education programs and preventive measures and give information for monitoring the caries which is helpful for policy makers